2020
DOI: 10.1016/j.jobe.2019.101033
|View full text |Cite
|
Sign up to set email alerts
|

Natural elements in the designer's work environment influence the creativity of their results

Abstract: It has been shown that the environment can determine the outcome of work that is carried out in it. Several studies have confirmed that an environment with natural elements can have beneficial effects on people's physical and psychological health and also improve their creativity. However, little research has addressed this effect on the creativity of design engineers within the specific context of processes involving the design of new products. The main purpose of this paper is to determine whether product de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 35 publications
(39 reference statements)
2
23
0
1
Order By: Relevance
“…Thus, de Kort et al (2006) showed that significant levels of stress reduction could be achieved when people were subjected to immersive simulated natural environments and, similarly, (Kjellgren and Buhrkall 2010) showed that the same effect could be achieved with both natural environments and other settings in which the natural elements were simulated. Fewer works have studied the effect that real or simulated natural environments can have on designers' creativity, specifically during the process of designing new products, although some very recent studies offer clues that also point in a similar direction to the works mentioned above (Chulvi et al 2020;Batey et al 2021).…”
Section: Research Backgroundmentioning
confidence: 97%
See 2 more Smart Citations
“…Thus, de Kort et al (2006) showed that significant levels of stress reduction could be achieved when people were subjected to immersive simulated natural environments and, similarly, (Kjellgren and Buhrkall 2010) showed that the same effect could be achieved with both natural environments and other settings in which the natural elements were simulated. Fewer works have studied the effect that real or simulated natural environments can have on designers' creativity, specifically during the process of designing new products, although some very recent studies offer clues that also point in a similar direction to the works mentioned above (Chulvi et al 2020;Batey et al 2021).…”
Section: Research Backgroundmentioning
confidence: 97%
“…A. Both natural and artificial environments enhance creativity during the design phase, compared with a neutral environment, but it has not been tested with a specific design method (Chulvi et al 2020). B.…”
Section: Research Backgroundmentioning
confidence: 99%
See 1 more Smart Citation
“…The time available to solve each problem was established in 40 min, since it has been proved that the frequency of idea production, during the creative stage of design, is constant during the first 60 min (Howard et al 2008). Similar studies use times within the range of 30-60 min for this kind of conceptual problem-solving experiences, like the ones carried out by Chulvi et al (2020)…”
Section: Design Experimentsmentioning
confidence: 99%
“…El tiempo disponible para resolver cada problema se estableció en 40 minutos, ya que se ha probado que la frecuencia de la producción de ideas, durante la etapa creativa del diseño, es constante durante los primeros 60 minutos (T. Howard et al, 2008). Estudios similares utilizan rangos de tiempo de entre 30 y 60 minutos para este tipo de experiencias de resolución conceptual de problemas, como los llevados a cabo por Chulvi, Agost, Felip, & Gual (2020) Así, los diseñadores noveles tuvieron que enfrentarse la etapa de resolución del problema de diseño, la cual consiste en actividades como la generación, evaluación y selección de la propuesta conceptual final para su futuro desarrollo (Blessing, 1994;Nidamarthi, Chakrabarti, & Bligh, 1997;Roozenburg & Eeckels, 1995). Durante este proceso, los participantes pudieron generar más de una alternativa para resolver el problema de diseño, pero al final de la experiencia, tuvieron que elegir una opción final, la que ellos consideraran que encajaba mejor con el problema propuesto.…”
Section: Figura 40 Desarrollo Del Experimento I (Imagen Propia)unclassified